A creation of U.P.C.D. orthodontic patient database management system - Narvaez, Vicente N.; Narvaez, Vicente N.
There is a requirement for effective management and record-keeping in today's orthodontic clinics. This paper discusses the principal requirements of a computer program for comprehensive orthodontic department and describes in detail the U.P.C.D. Orthodontic Patient Database Management System. The system design was based on the existing manual way of updating and keeping records in the U.P.C.D. Graduate Program in Orthodontics. A computer application was then developed for the U.P.C.D. Graduate Program in Orthodontics to store the patient records in computer. In this research, Visual Basic 6.0 was used to create and develop the user interface combined with MySQL as the database. The U.P.C.D Orthodontic Patient Database Management System was populated with sample records of 200 patients. The database system was stored with patient's demographic data (patient's name, address, age sex and etc.), medical and dental histories, diagnostic records, (casts models, intraoral and extra oral photographs,cephalomeric and panoramic radiographs, cephalometric tracings)and treatment records.The security, accuracy, speed and realiability of the U.P.C.D. Orthodontic Patient Database Management System were also evaluated. Based on the results of the trials, the conclusions that were drawn from the study are the following: (1) The U.P.C.D. OPDM System has improved the security of orthodontic patients' record, protecting it from unauthorized uses and abusive authorized uses. (2) U.P.C.D. OPDM System makes sorting and collecting information of orthodontic patients faster and accurate. (3) The U.P.C.D. OPDM System secures the patient's record from loss and allows indefinite record keeping.